The assessment of genetic variability and taxonomic affinity of local pummelo accessions from Yogyakarta, Indonesia based on RAPD - Ratna Susandarini; Rina Arifati; Abdul Razaq Chasani; Siiti Subandiyah (Universitas Gadjah Mada, 2014)
Pummelo (Citrus maxima) is one of three biotypes considered as true species within the genus Citrus.A major issue of pummelo taxonomy in Indonesia is the high number of cultivars showing variability inphenotypic characters but of unknown genetic diversity. In this study, the assessment of genetic variabilityand taxonomic affi nity of local accessions of C. maxima from Yogyakarta was examined based on RAPDfi ngerprinting. The availability of universal primers and technical simplicity makes RAPD as a molecular toolof choice for the assessment of genetic variability at various taxonomic levels. In this study, 13 accessions of C.maxima collected from Yogyakarta were observed for their genetic variability. An additional three registeredcultivars were included for comparative purpose. Two decamer primers used for the amplifi cation of DNAproduced 222 bands with 174 of them were polymorphic. The data was subjected to cluster analysis to observethe grouping of accessions and taxonomic affi nity. Results indicated high genetic variability among accessions.The dendrogram constructed using UPGMA method based on simple matching coeffi cient showed twomain clusters were which was in line to morphological characters. The grouping of accessions showed cleardifferentiation between accessions bearing white and those with reddish fruit fl esh, and thus demonstratestaxonomic value of this study in recognizing important agronomic character for this tropical fruit crop.